Enteroaggregative Escherichia coli quantification in children stool samples using quantitative PCR. Issue 7 (6th December 2012) - Lima, Ila Fernanda Nunes; Quetz, Josiane da Silva; Guerrant, Richard Littleton; Nataro, James P.; Houpt, Eric R.; Lima, Aldo Angelo Moreira; Havt, Alexandre
<x xml:space="preserve">Abstract</x> Enteroaggregative Escherichia coli (EAEC) is a common cause of infectious diarrhea, especially in children living in poor‐resource countries. In this article, we present a SYBR Green‐based real‐time polymerase chain reaction (qPCR) method for quantitative detection of EAEC in DNA directly extracted from human stool samples. To test the proposed qPCR system, we examined specificity, sensitivity, repeatability, and also the degree of DNA extraction efficiency using EAEC strain 042 spiked into EAEC‐free stool sample. The specificity of this assay was proved using six strains of EAEC, seven strains of other E. coli types, and one strain of Shigella. The detection limit of qPCR was 67 CFU/reaction. In naturally infected stool samples, we found EAEC in quantities varying from 6.7 × 105 to 2 × 109 CFU/g of feces. We could not detect any reduction after stool DNA extraction for the amounts of 107 and 106 CFU/mL of spiked EAEC. This qPCR assay is simple, rapid, reproducible, sensitive, specific, and allows rapid EAEC quantification to be used in a variety of further EAEC studies. This new quantitative method provides a relatively simple means to quantify EAEC, which will likely be key to understanding the pathophysiology and impact of EAEC infection.